VD_FINDINFO Décision / 2018 / 679 vom 27. August 2018 - VD Tribunal cantonal (2018)
PARTIE CIVILE, PLAIGNANT, CAPACITÉ D'ÊTRE PARTIE, PARTIE À LA PROCÉDURE | 116 CPP (CH), 117 CPP (CH), 122 al. 2 CPP (CH)